Cryptic diversity of cellulose-degrading gut bacteria in industrialized humans - Moraïs, Sarah; Winkler, Sarah; Zorea, Alvah; Levin, Liron; Nagies, Falk S. P.; Kapust, Nils; Lamed, Eva; Artan-Furman, Avital; Bolam, David N.; Yadav, Madhav P.; Bayer, Edward A.; Martin, William F.; et al. (Science (American Association for the Advancement of Science), 2024)
Humans, like all mammals, depend on the gut microbiome for digestion of cellulose, the main component of plant fiber. However, evidence for cellulose fermentation in the human gut is scarce. We have identified ruminococcal species in the gut microbiota of human populations that assemble functional multienzymatic cellulosome structures capable of degrading plant cell wall polysaccharides. One of these species, which is strongly associated with humans, likely originated in the ruminant gut and was subsequently transferred to the human gut, potentially during domestication where it underwent diversification and diet-related adaptation through the acquisition of genes from other gut microbes. Collectively, these species are abundant and widespread among ancient humans, hunter-gatherers, and rural populations but are rare in populations from industrialized societies thus indicating potential disappearance in response to the westernized lifestyle. The guts of urbanized people worldwide are known to contain less microbial biodiversity than those of humans living rurally. The worry is that the loss of key species contributes to the increasing prevalence of poor metabolic health among urbanized people. By searching for key genes involved in cellulose degradation in metagenome-assembled genomes, Moraïs et al . discovered cellulolytic bacteria in humans. All candidate Ruminococcus species assembled active cellulosomes, enzyme complexes capable of degrading microcrystalline cellulose. Three species were distinguished with phylogenies indicating derivation from primate and ruminant hosts, and they showed specific host preferences and ongoing host adaptation. The occurrence of cellulolytic bacteria in humans reveals that a complicated process of dynamic co-evolution occurs in the gut and is possibly regulated by environment. —Caroline Ash Cellulolytic human gut bacteria are scarce in urban societies but abundant in ancient and hunter-gatherer microbiomes.